The landscape of lysogeny across microbial community density, diversity and energetics. (22nd June 2021) - Silveira, Cynthia B.; Luque, Antoni; Rohwer, Forest
Summary: Lysogens are common at high bacterial densities, an observation that contrasts with the prevailing view of lysogeny as a low‐density refugium strategy. Here, we review the mechanisms regulating lysogeny in complex communities and show that the additive effects of coinfections, diversity and host energic status yield a bimodal distribution of lysogeny as a function of microbial densities. At high cell densities (above 10 6 cells ml −1 or g −1 ) and low diversity, coinfections by two or more phages are frequent and excess energy availability stimulates inefficient metabolism. Both mechanisms favour phage integration and characterize the Piggyback‐the‐Winner dynamic. At low densities (below 10 5 cells ml −1 or g −1 ), starvation represses lytic genes and extends the time window for lysogenic commitment, resulting in a higher frequency of coinfections that cause integration. This pattern follows the predictions of the refugium hypothesis. At intermediary densities (between 10 5 and 10 6 cells ml −1 or g −1 ), encounter rates and efficient energy metabolism favour lysis. This may involve Kill‐the‐Winner lytic dynamics and induction. Based on these three regimes, we propose a framework wherein phage integration occurs more frequently at both ends of the host density gradient, with distinct underlying molecular mechanisms (coinfections and host metabolism) dominating at each extreme.